2005
DOI: 10.1002/srin.200506058
|View full text |Cite
|
Sign up to set email alerts
|

Reoxidation of Ni‐ and Ni‐Fe‐Alloys by Al2O3‐SiO2 Refractory Materials

Abstract: Reactions at the refractory/melt interface during ingot casting of Ni-and Ni-Fe-alloys were studied. The casts were performed using different alumino-silicate bricks as refractory materials. Samples taken from the casting channel before and after casting were investigated using light and scanning electron microscopy with XPS. Thermodynamic calculations were performed with FactSage and the results were compared with the results from industrial tests. After the melt has infiltrated the surface layer of the brick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A number of potential sources can lead to generation of new inclusions, such as reoxidation [1,2] , reaction between steel and runner refractory [3,4], While a number of sources could supply oxygen for reoxidation, the pickup of oxygen by the steel stream from the surrounding atmosphere is one of the most important. [5][6][7] Industrial studies have evidently shown that using a protective shroud of inert gas such as argon can reduce the number of inclusions and lower the nitrogen as well as hydrogencontents in the steel [8,9] . Some efforts have been made to understand and describe the oxygen pickup around the teeming steel stream.…”
Section: Introductionmentioning
confidence: 99%
“…A number of potential sources can lead to generation of new inclusions, such as reoxidation [1,2] , reaction between steel and runner refractory [3,4], While a number of sources could supply oxygen for reoxidation, the pickup of oxygen by the steel stream from the surrounding atmosphere is one of the most important. [5][6][7] Industrial studies have evidently shown that using a protective shroud of inert gas such as argon can reduce the number of inclusions and lower the nitrogen as well as hydrogencontents in the steel [8,9] . Some efforts have been made to understand and describe the oxygen pickup around the teeming steel stream.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies 3–22 were carried out to find the possible sources for non‐metallic inclusions. Inclusions were also found to be generated in the casting process.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusions were also found to be generated in the casting process. For example, reoxidation during transfer from the ladle to the runner system 3–9, interaction between the steel and the refractory material in the runner system 5–7, 10, 11, 22, reoxidation inside the mould 3, 5, 6, 19 and the mould powder 4, 5, 12, 13 were all been reported the sources of non‐metallic inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of potential sources can lead to generation of new inclusions, such as reoxidation, 1–2 reaction between steel and runner refractory 3–7, flushing‐off of refractory and entrainment of casting powder 6, 8–10. While a number of sources could supply oxygen for reoxidation, the pickup of oxygen by the steel stream from the surrounding atmosphere is one of the most important 6, 8, 11, 12.…”
Section: Introductionmentioning
confidence: 99%